Trends in health behaviors and mental health among Korean adolescents in Korea over 5 years, 2017–2021: focusing on the comparisons before and during the COVID-19 pandemic - Lee, Mi-Sun; Kim, Dong Jun; Lee, Hooyeon (Frontiers in Public Health, 2023)
Objectives We investigated recent trends in health behaviors and mental health conditions among Korean adolescents from 2017 to 2021 and compared the changes before and during the coronavirus disease 2019 (COVID-19) pandemic. Methods Data analysis was conducted on 289,415 adolescents participating in the Korea Youth Risk Behavior Web-Based Survey, an annual cross-sectional study from 2017 to 2021. All analysis was conducted using sex stratification, and the annual percentage change (APC) was calculated. Results Alcohol consumption and smoking decreased in the first year of the COVID-19 pandemic compared with before, except for girls from the low-income level. The prevalence of inadequate physical activity for both boys and girls increased in 2020 compared with the pre-COVID-19 period and decreased again by 2021. The prevalence of obesity in both sexes increased regardless of the period (boys, APC = 8.2%, 95% confidence intervals (CI), 6.4–10.1; girls, APC = 3.3%, 95% CI, 1.8–4.8). The prevalence of stress, depression, and suicidal ideation, plans, and attempts for both sexes decreased in 2020 compared to the pre-COVID-19 period. By 2021, this prevalence had returned to a level similar to before the pandemic. No significant APC changes were observed in the prevalence of mental health. Conclusions These findings demonstrate the trends and APCs in health behaviors and mental health conditions among Korean adolescents over the last 5 years. We must pay attention to the heterogeneous and multifaceted features of the COVID-19 pandemic.